Efficacy of balloon Eustachian tuboplasty as a first line treatment for otitis media with effusion in children - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2020)
Objective This study aimed to compare the outcomes of ventilation tube insertion and balloon Eustachian tuboplasty as a first line treatment for otitis media with effusion in children. Method This was a retrospective evaluation of 62 children, 30 cases that underwent balloon Eustachian tuboplasty (group 1) and 32 cases that underwent ventilation tube insertion (group 2), from July 2016 to April 2018. Results The pre-operative air-bone gap of patients who underwent balloon Eustachian tuboplasty was 15-35 dB (mean: 27.6 +/- 8.2 dB). The mean pre-operative air-bone gap decreased to 9.6 dB after a mean of 14.4 months (p < 0.05). The air-bone gap decreased from 25.6 dB to 17.6 dB in the ventilation tube group. There was a significant improvement in the air-bone gap values in both groups; however, this decrease was significantly higher in the balloon Eustachian tuboplasty group (p = 0.043). Conclusion Balloon Eustachian tuboplasty may be an effective and safe method for use as a first-line treatment of otitis media with effusion in children.
Keywords: Eustachian Tube Dysfunction; Otitis Media With Effusion; Balloon Dilatation Eustachian Tuboplasty; Ear; Middle; DILATION; TUBE; DILATATION; OUTCOMES